Study on Online Purchase Decisions on The Online Shopee Selling Site - Herawati, Ratna; Chasanah, Amalia Nur; Perdana, Tito Aditya; Wardhani, Masitha Fahmi (Future Science, 2020)
The state of the environment for consumers to get information, namely electronic word of mouth and the promotional mix will affect consumer decision-making when shopping. This study aims to determine the effect of promotional mix variables and electronic word of mouth on purchasing decisions on the online buying and selling site Shopee. Promotion mix variables used are advertising and sales promotion. The sample used in this study were Semarang residents who had shopped on the Shopee online buying and selling site with a sample size of 100. The data analysis technique used was multiple regression with the classical assumptions of multicollinearity, autocorrelation, heteroscedasticity, and normality. The results showed that the variables of advertising, sales promotion, electronic word of mouth had a significant positive effect on online purchasing decisions. The adjusted r square value is 0.496, which means that the variables of advertising, sales promotion, and electronic word of mouth can explain online purchasing decisions by 49.6%. In contrast, the rest is explained by other variables, not in this study.